How well do we know green gentrification? A systematic review of the methods. (August 2022) - Quinton, Jessica; Nesbitt, Lorien; Sax, Daniel
This systematic literature review identifies and critiques methodological trends in green gentrification research (focusing on studies of vegetative greening) and provides suggestions for advancing this field. Findings reveal (1) research has largely focused on U.S. case studies; (2) early work employed qualitative methods but quantitative analyses have become more common; (3) little attention has been paid to the influence of greening characteristics/functions and non-greening factors on gentrification; (4) the mechanisms through which greening leads to gentrification are not well understood, particularly on the demand side; and (5) despite being the main concern of green gentrification, displacement has not been well-documented.